Factors that influence the postural balance on institutionalized elderly: a cross-sectional study - Pereira, Natalia Moya Rodrigues; Araya, Marcel Jean Pierre Massè; Chagas, Eduardo Federigui Baisi; Scheicher, Marcos Eduardo (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Introduction: Older adults living in Nursing Homes are a complex population, with a high prevalence of dependency in activities of daily living, multimorbidity, polypharmacy, and reduced mobility and poor balance when compared with community-dwelling elderly. Objectives: The aim of this study was to investigate if the postural balance of institutionalized elderly is influenced by the length of institutionalization, age, number of medications, number of falls, body mass index (BMI) and cognitive status. Methods: 98 elderly people living in the three Nursing Homes were evaluated and 45 were included. Were considered the following variables: ages over 60 years old; length of institutionalization, falls in the previous year, anthropometric measurements (height and weight) and cognitive status. The balance was evaluated by Berg Balance Scale (BBS) and by the Short Physical Performance Battery (SPPB). Results: Of all the variables evaluated, only number of medication and BMI had a negative correlation with scores of BBS and SPPB. In the regression analysis, the significant effect of the number of medications on the SPPB and BERG scores was confirmed. Conclusion: Elderly people living in nursing homes have a poor postural balance and the number of medications and BMI contribute significantly to this.